From Manual to Modern: Integrating e-Budgeting and e-Reporting for Efficient School Fund Management - Endah Reknaningsih; Nurkolis Nurkolis; Muhammad Prayito (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This research aims to develop an integrated e-Budgeting and e-Reporting system for managing BOS funds at schools. The study's background highlights the persistent challenges in manual management of BOS funds, including reporting delays, data inconsistencies, and administrative errors. These inefficiencies emphasize the need for a digital solution that integrates budgeting, reporting, and monitoring functions. The research method employed a Research and Development (R&D) approach, using needs analysis, system design, prototype development, expert validation, and limited field testing. The results indicate that the system achieved a feasibility score of 3.52/4 (88.8%), categorized as highly feasible with minor revisions. Limited field testing yielded an average score of 3.68/4, with reporting time efficiency improving by approximately 40% and administrative errors reduced through automated validation features. The developed system effectively integrates budgeting and reporting processes into a single platform, enhancing data accuracy, transparency, and efficiency. This study contributes to the field of digital financial governance in education and provides practical insights for implementing integrated digital systems in resource-constrained schools. Future research could explore the system’s long-term impacts and scalability across diverse educational settings.